Genomics—based approaches may assist in the verification and accelerate responsible deployment of marine carbon dioxide removal - Hook, Sharon E.; Bodrossy, Levente; Brewer, Elizabeth A.; Willis, Anusuya (Frontiers in Climate, 2024)
Rapid development and deployment of marine carbon dioxide removal (mCDR) approaches will be required to prevent the worst consequences of climate change and meet national treaty obligations under the Paris agreement. However, approaches to monitor the efficacy and environmental safety of mCDR are not being developed with the same intensity as the technology. Verification will be required to convince a sceptical public and regulatory community of the overall benefit of mCDR as well as provide the regulatory community a basis for risk assessments that will be required for at scale deployments. In this perspective, we posit that genomics-based approaches can be used to assess the efficacy of carbon sequestration and monitor for the possibility of unintended consequences. By adopting these approaches, it will be feasible to develop the evidence portfolio necessary to underpin assessments of the risks, benefits and trade-offs involved in responsible deployment of mCDR.